Improved nanoformulation and bio-functionalization of linear-dendritic block copolymers with biocompatible ionic liquids. Issue 16 (1st April 2022) - Hamadani, Christine M.; Chandrasiri, Indika; Yaddehige, Mahesh Loku; Dasanayake, Gaya S.; Owolabi, Iyanuoluwani; Flynt, Alex; Hossain, Mehjabeen; Liberman, Lucy; Lodge, Timothy P.; Werfel, Thomas A.; Watkins, Davita L.; Tanner, Eden E. L.
Abstract : Ionic liquid-functionalized linear-dendritic block copolymer nanoparticles show facile assemblies and red blood cell hitchhiking in whole blood. Abstract : Linear-dendritic block copolymers (LDBCs) have emerged as promising materials for drug delivery applications, with their hybrid structure exploiting advantageous properties of both linear and dendritic polymers. LDBCs have promising encapsulation efficiencies that can be used to encapsulate both hydrophobic and hydrophilic dyes for bioimaging, cancer therapeutics, and small biomolecules. Additionally, LDBCS can be readily functionalized with varying terminal groups for more efficient targeted delivery. However, depending on structural composition and surface properties, LDBCs also exhibit high dispersities ( Đ ), poor shelf-life, and potentially high cytotoxicity to non-target interfacing blood cells during intravenous drug delivery. Here, we show that choline carboxylic acid-based ionic liquids (ILs) electrostatically solvate LDBCs by direct dissolution and form stable and biocompatible IL-integrated LDBC nano-assemblies. These nano-assemblies are endowed with red blood cell-hitchhiking capabilities and show altered cellular uptake behavior ex vivo . When modified with choline and trans -2-hexenoic acid, IL-LDBC dispersity dropped by half compared to bare LDBCs, and showed a significant shift of the cationic surface charge towards neutrality. Proton nuclear magnetic resonance spectroscopy evidenced twice the total amount of IL on the LDBCs relative to an established IL-linear PLGA platform. Transmission electron microscopy suggested the formation of a nanoparticle surface coating, which acted as a protective agent against RBC hemolysis, reducing hemolysis from 73% (LDBC) to 25% (IL-LDBC). However, dramatically different uptake behavior of IL-LDBCs vs. IL-PLGA NPs in RAW 264.7 macrophage cells suggests a different conformational IL-NP surface assembly on the linear versus the linear-dendritic nanoparticles. These results suggest that by controlling the physical chemistry of polymer-IL interactions and assembly on the nanoscale, biological function can be tailored toward the development of more effective and more precisely targeted therapies.